Action, knowledge and embodiment in Berkeley and Locke. (2nd January 2018) - Stoneham, Tom
Abstract : Embodiment is a fact of human existence which philosophers should not ignore. They may differ to a great extent in what they have to say about our bodies, but they have to take into account that for each of us our body has a special status, it is not merely one amongst the physical objects, but a physical object to which we have a unique relation. While Descartes approached the issue of embodiment through consideration of sensation and imagination, it is more directly reached by consideration of action and agency: whenever we act upon the world, we act by moving our bodies. So if we can understand what an immaterialist such as Berkeley thinks about agency, we will have gone a fair way to understanding what he thinks about embodiment. §1 discusses a recent flurry of articles on the subject of Berkeley's account of action. I choose to present Berkeley as a causal-volitional theorist (realist) not because I think it is the uniquely correct interpretation of the texts, but because I find it more philosophically interesting as a version of immaterialism. In particular, it raises the possibility of a substantive account of human embodiment which is completely unavailable to the occasionalist. §2 articulates an apparent philosophical problem for Berkeley qua causal-volitional theorist and show that Locke was aware of a related problem and had a solution of which Berkeley would have known. §3 distinguishes two interpretations of Berkeley's famous denial of blind agency – as the assertion of a weak representational condition or a strong epistemic one – and provide evidence that there was a well-established debate about blind powers in the seventeenth century which took the metaphor of blindness as indicating an epistemic rather than merely representational failing. What remains to do in §4 is to consider whether Berkeley, with his own peculiar commitments, could in fact accept this account of agency.